The effect of developmentally supportive positioning (DSP) on preterm infants' stress levels - Angie Hennessy; Carin Maree; Piet Becker (AOSIS, 2007)
Research has proven that developmentally supportive care (DSC) improves the developmental outcomes for preterm infants. ABSTRAK Navorsing het bewys dat ontwikkeling-ondersteunende sorg (OOS) die ontwikkelingsuitkomste van premature babas verbeter.